Income inequality, relative poverty and spatial segregation: Scotland and West Central Scotland in context - Martin Taulbut (Luxembourg Income Study (LIS), 2011)
Mortality in West Central Scotland is generally higher than, and improving at a slower rate, than European regions which have experienced comparable levels of deindustrialisation. This paper uses data from the Luxemburg Income Study and other sources to consider whether income inequality, relative poverty and spatial segregation might contribute to this phenomenon. Measured by the Gini Coefficient, income inequality in Scotland is high in European terms, though comparable to levels seen in Wales, Northern Ireland and the Irish Republic. At the regional level, levels of income inequality in WCS are high compared to all the mainland European postindustrial regions; this is especially true in relation to the East German regions. There is less certainty over whether it is high compared to other UK post-industrial regions. These higher levels of income inequality feed through into high levels of relative poverty. Based on data from 1994-2001, relative poverty in WCS was high compared to levels found in the East European, German and Benelux regions (but similar to levels observed in Nord-Pas-de-Calais, Merseyside and Wales). However, spatial inequalities in relative poverty in WCS appear to be lower than in Merseyside.
Keywords: 330